Peer Tutor Method in Improving the Ability to Do English Conversation Assignments in High School Students - Kiều Linh Trang (Newinera Publisher, 2022)
The purpose of this research was to examine whether or not high school students may benefit from using a peer tutor to improve their English conversation skills. High school students were the subjects of this study that combined qualitative and quantitative approaches to data gathering and analysis. Significant improvements in students' English conversation abilities throughout the course of the study backed up the researchers' conclusion that the peer tutor technique was helpful in helping high school students learn the language. Student interest and engagement, peer support and cooperation, and personalized feedback and assistance all play a role in the peer tutoring method's success. Discussion of the study's implications for educators and language instructors was included, with a focus on how the peer tutor technique might increase students' interest and motivation in language learning and the need for further study in this area. The abstract wrapped up with a summary of the study's key findings, which centered on the peer tutoring approach's efficacy in improving high school students' proficiency in English conversation. The abstract was well written, providing prospective readers with a short summary of the study's aims, methodology, and findings.